OP84 Estimating the health benefits of a sugary drinks duty in England. (2nd September 2014) - Collins, B; O'Flaherty, M; Bromley, H; Lloyd-Williams, F; Razzaq, A; Capewell, S
Abstract : Background: Sugar is seen by some as the next "public health frontier". Indeed, increasing evidence associates excess refined sugar intakes with obesity, type 2 diabetes and heart disease. Worryingly, the estimated volume of sugary drinks purchased in the UK has more than doubled between 1975 and 2007, from 510ml to 1140ml per person per week. Might a fiscal intervention promote public health? In this study, we therefore aimed to quantify the potential benefits of putting a duty on sugary drinks. Methods: We accessed National Diet and Nutrition Survey (NDNS) data and drinks manufacturers' sales data on sugar sweetened beverages (SSBs). We then modelled plausible low, mid and high intake policy scenarios; combining this with data from two recently published models of obesity and associated diseases and Quality Adjusted Life Years (QALYs). We assumed a linear relationship between calories consumed, rates of obesity and obesity-related diseases, specifically diabetes, stroke and coronary heart disease (CHD), and cancer. We then conducted rigorous sensitivity analyses. Results: In England, we estimated that a 20% SSB duty could reduce average energy consumption by approximately 8kcal per person per day. That mid consumption policy scenario might cut obesity rates by 1% (from 24.1% to 23.9% of adults) which equates to approximately 100, 000 fewer obese people. This duty would result in approximately: 60, 000 fewer cases of diabetes per year; 41, 000 fewer cases of CHD and stroke per year; 11, 000 fewer cases of cancer per year; one million QALYs gained per year; and £18 million in healthcare cost savings per year. In terms of parameters, the main driving factor for the potential reduction in obesity and associated disease was the level of SSB consumption in the population. For the low and high consumption scenarios respectively, a 20% duty could cut obesity by an estimated 0.5%–1.5%, with approximately 495, 000–1.5 million QALYs gained and £9million–£28 million in healthcare cost savings per year. Conclusion: A 20% duty on sugary drinks could dramatically reduce the obesity disease burden and also achieve substantial savings. Our findings support the Sustain report which recently estimated that a 20% duty could generate up to £1billion in annual tax revenues. Such revenues could be spent on interventions to improve health, such as subsidised healthy foods, food growing co-ops, walking and cycling.